Revisión sobre las infecciones no bacterianas del aparato respiratorio: neumonías víricas - Galván, José María (Arch Bronconeumol, 2015)
Although bacteria are the main pathogens involved in community-acquired pneumonia, a significant number of community-acquired pneumonia are caused by viruses, either directly or as part of a co-infection. The clinical picture of these different pneumonias can be very similar, but viral infection is more common in the pediatric and geriatric populations, leukocytes are not generally elevated, fever is variable, and upper respiratory tract symptoms often occur; procalcitonin levels are not generally affected. For years, the diagnosis of viral pneumonia was based on cell culture and antigen detection, but since the introduction of polymerase chain reaction techniques in the clinical setting, identification of these pathogens has increased and new microorganisms such as human bocavirus have been discovered. In general, influenza virus type A and syncytial respiratory virus are still the main pathogens involved in this entity. However, in recent years, outbreaks of deadly coronavirus and zoonotic influenza virus have demonstrated the need for constant alert in the face of new emerging pathogens. Neuraminidase inhibitors for viral pneumonia have been shown to reduce transmission in cases of exposure and to improve the clinical progress of patients in intensive care; their use in common infections is not recommended. Ribavirin has been used in children with syncytial respiratory virus, and in immunosuppressed subjects. Apart from these drugs, no antiviral has been shown to be effective. Prevention with anti-influenza virus vaccination and with monoclonal antibodies, in the case of syncytial respiratory virus, may reduce the incidence of pneumonia.